Pulp and viscose rayon manufacture an integrated plant - Chua, Benjamin Jr; See, Benito; Yap, James; Yu, Robert (College of Engineering, 1962)
The proposed plant has a capacity of 5 tons viscose rayon and 10 tons pulp both of which is on the day basis or a total of P10,728,500.00. However, in order to achieve this a huge capital is needed, P7,642,089.00. Selling the yard at its current price of P3.00 per pound and the pulp at P410.00 per ton will bring in a profit of P2,357,271.00 before taxes. The break-even point is at 29.7% of maximum operating capacity. Shut-down point is at 10.5% of maximum operating capacity. Pay-out time is 2.35 years. Per cent return on investment is 32.65%.